Picking up the pieces - Calvert, Patricia (New York : Scribner's ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
A girl who has suffered a paralyzing spinal cord injury begins the process of emotional healing. (Gr. 6-9)
940
Accelerated Reader AR
Keywords: Disabilities -- Fiction; Self-acceptance -- Fiction